Blunted Pressure Natriuresis in the Brattleboro Diabetes Insipidus Rat - Gonzalez-Campoy, Michael J.; Awazu, Midori; Granger, Joey P.; Haas, John A.; Romero, Carlos J.; Knox, Franklyn G. (Hypertension (Dallas, Tex. 1979), 1989)
Antidiuretic hormone is known to stimulate the renal synthesis of prostaglandins. These autacoids, in turn, modulate the pressure natriuresis phenomenon. Accordingly, the present study was done to test the hypothesis that, in the absence of antidiuretic hormone and antidiuretic hormone-dependent prostaglandin synthesis, the pressure natriuresis response is blunted. Experiments were performed on Brattleboro diabetes insipidus rats (n=7) and Long Evans control rats (n=14). A change in perfusion pressure in the Long Evans rats from 89.3±1.0 to 108.7±1.1 mm Hg (p<0.05) was associated with significant increases in the fractional excretion of sodium (1.1±0.2 to 2.3±0.3%) and the urinary prostaglandin excretion (32.6±6.8 to 56.6±10.0 pg/min). In contrast, a similar change in perfusion pressure in the diabetes insipidus rat from 88.6±1.4 to 106.2±1.5 mm Hg (p<0.05) resulted in no significant increases in either sodium or prostaglandin excretions. Treatment of a third group of diabetes insipidus rats (n=9) with 1-desamino-8-D-arginine vasopressin (1 μg/day) restored the natriuretic response to increases in renal perfusion pressure. Treated diabetes insipidus and Long Evans control rats had comparable natriuretic responses to increases in renal perfusion pressure. Untreated diabetes insipidus rats, on the other hand, had blunted responses. In summary, the pressure natriuresis response in diabetes insipidus rats is blunted compared with Long Evans control rats. We conclude that antidiuretic hormone is necessary for the complete expression of the pressure natriuresis response. (Hypertension 1989;13:322-326)